Applications of Surface-Enhanced Raman Scattering in Biochemical and Medical Analysis - Szaniawska, Aleksandra; Kudelski, Andrzej (Frontiers in Chemistry, 2021)
In this mini-review, we briefly describe certain recently developed applications of the surface-enhanced Raman spectroscopy (SERS) for determining various biochemically (especially medically) important species from ones as simple as hydrogen cations to those as complex as specific DNA fragments. We present a SERS analysis of species whose characterization is important to our understanding of various mechanisms in the human body and to show its potential as an alternative for methods routinely used in diagnostics and clinics. Furthermore, we explain how such SERS-based sensors operate and point out future prospects in this field.